2012
DOI: 10.1134/s1063784212070092
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the size and shape of polydisperse dust particles in a complex glow discharge plasma

Abstract: The size and shape factor distribution of levitating particles is studied by the method of extraction of dust particles from the discharge chamber. Two dust traps existing in a glow discharge in the strata and above the lower wall of the tube near the bend in the current channel are investigated separately. It is found that the size distribution of polydisperse particles of an arbitrary shape is of the bimodal type due to simultaneous levitation of particles with two shape factors. Polydisperse spherical parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…We studied exactly levitated particles, and the method of extraction of those trapped in the stratum of the glow discharge was worked out in Refs. .…”
Section: Introductionmentioning
confidence: 99%
“…We studied exactly levitated particles, and the method of extraction of those trapped in the stratum of the glow discharge was worked out in Refs. .…”
Section: Introductionmentioning
confidence: 99%
“…This experimental setup was previously used for selecting particles with respect to shape and size [7][8][9]. In the present study, we have used particles of melamine-formaldehyde resin (MF-R) with a density of 1.5 g/cm 3 and average initial diameter of 7.8 μm.…”
mentioning
confidence: 99%
“…The results show that both conductive particles with a diameter of less than 10-8 mm and dust particles in the air will reduce the discharge initiation voltage and breakdown voltage of the gas [17]. Ermolenko et al simulated and analysed with the influence of multiphase medium on the electric field of plasma reactor by finite element method, and proposed that water droplets/metal particles in the air gap can seriously distort the surrounding electric field, resulting in the formation of small corona area of air medium [18]. Yi et al found that many haze and haze external insulation discharge accidents in Guangzhou Power Grid include both insulator surface flashover caused by wet settlement and air gap breakdown discharge [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ermolenko et al. simulated and analysed with the influence of multiphase medium on the electric field of plasma reactor by finite element method, and proposed that water droplets/metal particles in the air gap can seriously distort the surrounding electric field, resulting in the formation of small corona area of air medium [18]. Yi et al.…”
Section: Introductionmentioning
confidence: 99%